FRI0602 What is the Relation Between Clinical Syndromes and Brain MRI Changes in Npsle? A Systematic Review and Meta-Analysis. (9th June 2015) - Amin, O.; Kaul, A.; Smith, T.; Howe, F.; Sofat, N.
Abstract : Background: The relationship between clinical NPSLE features and MRI findings is unclear. We used a systematic review and meta-analysis to overcome the limitations of previous studies which often use small patient numbers. As no single test can currently diagnose NPSLE, establishing a relationship between clinical disease manifestations and imaging may improve diagnosis, management and prognosis. Objectives: To conduct a systematic review and meta-analysis on all published studies of NPSLE which included data on MRI and 1999 ACR defined clinical NPSLE syndromes to determine their relationship. Methods: A systematic literature search of PUBMED MEDLINE (1947-), OVID MEDLINE (1946-), EMBASE (1980-) and COCHRANE (1998-) databases was undertaken to screen abstracts up to December 2014. Shortlisted studies contained key words (NPSLE; MRI) with MRI imaging and extractable results for individual clinical syndromes. Reviews, case reports, letters to the editor and studies not published in English or in human subjects were excluded. The CASP tool was used for quality assessment of the included studies. Data analysis used PRISM software and the Mann-Whitney test for statistical analysis. Results: Of 724 studies screened, 21 fulfilled inclusion criteria. In total 818 patients (91% female) with 1064 NPSLE syndromes were analysed. The 6 most prevalent syndromes were headache (19.6%), seizures (15.0%), cerebrovascular disease (14.0%), cognitive dysfunction (11.8%), acute confusional state (9.9%) and mood disorders (8.7%). Mononeuropathy, plexopathy, autonomic disorder and Guillain-Barré syndrome were rare (<1%). White matter hyperintensities (WMH) (Range 32.9-42.3%) and vascular lesions (15.4-31.7%) were the commonest MRI changes. Grey matter hyperintensities (GMH) (2.8-14.4%) were less frequent. There was a statistically significant association between an abnormal MRI result and cerebrovascular disease (p=0.0012) and cognitive dysfunction (p=0.0102). Conclusions: In this systematic review and meta-analysis, we found an association between abnormal MRI scans, cerebrovascular disease and cognitive dysfunction. NPSLE is a difficult clinical challenge and our finding is useful in guiding diagnosis and treatment. In future, advanced MRI techniques such as diffusion tensor imaging and 1H MR spectroscopy which probe tissue microstructure and metabolism or more objective clinical diagnostic tests might promote a better understanding between imaging changes and clinical changes in NPSLE. References: The American College of Rheumatology nomenclature and case definitions for neuropsychiatric lupus syndromes. Arthritis Rheum. 1999;42(4):599–608. Disclosure of Interest: None declared